It is asked to be prove:


1 Step

p(n) is assumed to be true for n=1


Meaning that it is only consider the first term on the left, and only the $2^n\cdot1$ consider in the right hand.


$$2=2 \square$$



What happens with n=3 for example?

My guess:


$$(n+1)(n+2)(n+3)=2^n\cdot1\cdot3\cdot5$$ $$(3+1)(3+2)(3+3)=2^3\cdot1\cdot3\cdot5$$ $$120=120?$$

Step 2

Assuming that the proposition is also valid for p(k)


Step 3

Making the induction of validity for k+1 to also be true.




Is this the right substation?


2 Answers 2


(a) is the correct way of thinking about it. You said it yourself, you are looking at the $n=3$ case, so you have to plug that into the given equation. (b) is incorrect because $n$ to be a range of numbers ($n=1,2,3$) when you need it to just be one ($n=3$).


You seem to have gotten rid of the (b) option. So then, yes that is the correct way of thinking about it for $n = 3$.


Hint: Here is what you want to prove. That is, when you replace $k$ with $k+1$, you obtain the following equation for $p(k+1)$:

$$ ((k+1)+1)((k+1)+2)((k+1)+3)\ldots((k+1)+(k+1))\\ =\\ 2^{k+1}\cdot1\cdot3\cdot5\cdot\ldots\cdot(2k-1)\cdot(2(k+1)-1) $$

Simplifying it a bit, this is equivalent to:

$$ (k+2)(k+3)(k+4)\ldots(2k+2) = 2^{k+1}\cdot1\cdot3\cdot5\cdot\ldots\cdot(2k-1)\cdot(2k+1) $$

Hopefully you can see how to finish off the induction now.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.